Dog days - Kinney, Jeff (Kinney, Jeff. Diary of a wimpy kid ;, 2009)
In the latest diary of middle-schooler Greg Heffley, he records his attempts to spend his summer vacation sensibly indoors playing video games and watching television, despite his mother's other ideas.